Evaluación de la producción de biogás a partir de la degradación de gallinaza sometida a diferentes relaciones C/N - Belduma Zambrano, Andrea Mercedes (2015)
The present research work entitled: EVALUATION OF PRODUCTION BIOGAS FROM MANURE DEGRADATION SUBJECT TO DIFFERENT RELATIONS C / N, was made taking into account animal production intensive systems that exist in the province of El Oro, the main objective is to evaluate the production of biogas from manure degradation subject to different relations C / N, and this way obtain a more beneficial economic activity and less pollutant, the methodology employed was the use of digesters in which organic waste is deposited considering the carbon / nitrogen ratio, and treated to decompose under anaerobic process that it is what generates biogas.